2014
DOI: 10.1111/ecog.01283
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the ecological causes of dispersal in a butterfly

Abstract: Dispersal, i.e. movements potentially leading to gene flow, is central in evolutionary ecology. Many factors can trigger dispersal, all linked to the social and/or the environmental context. Moreover, it is now widely demonstrated that phenotypes with contrasted dispersal abilities coexist within populations of a same species. The current challenge is to elucidate how social and environmental factors will influence the dispersal decision of individuals with distinct phenotypes. We have used the Metatron, a uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 60 publications
(83 reference statements)
14
90
1
Order By: Relevance
“…In agreement with our results, a number of various observations from short-term studies on butterfly movement and dispersal have suggested that weather may indeed drive dispersal rates (e.g. [22,27,29,30,42,43]). …”
Section: Discussion (A) Weather and Dispersalsupporting
confidence: 93%
“…In agreement with our results, a number of various observations from short-term studies on butterfly movement and dispersal have suggested that weather may indeed drive dispersal rates (e.g. [22,27,29,30,42,43]). …”
Section: Discussion (A) Weather and Dispersalsupporting
confidence: 93%
“…External factors include habitat quality and abiotic conditions such as temperature (Legrand et al, 2015;Kuussaari et al, 2016). External factors include habitat quality and abiotic conditions such as temperature (Legrand et al, 2015;Kuussaari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the large white butterfly (Pieris brassicae) has been used to explore the drivers of dispersal (Legrand et al 2015). This species exhibits a dispersal syndrome where dispersers and residents differ phenotypically.…”
Section: Dispersal Syndromesmentioning
confidence: 99%
“…This behaviour, which is likely heritable, would thus increase the efficiency of movement between patches and reduce the time-and risk-associated costs of dispersal Larranaga et al 2013). Dispersers are therefore not a random fraction of the population, but are rather individuals with covarying morphological and behavioural traits that describe variation in dispersal in P. brassicae (Legrand et al 2015).…”
Section: Dispersal Syndromesmentioning
confidence: 99%
See 1 more Smart Citation